2021
DOI: 10.3390/polym13060940
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation on the Surface of (Poly)Ether-Ether-Ketone and In Vitro Antimicrobial Efficacy of Photodynamic Therapy on Peri-Implant Mucositis

Abstract: Poly-ether-ether-ketone (PEEK) is an aesthetically pleasing natural material with good biocompatibility and shock absorption characteristics. The application of PEEK as a dental implant or abutment is expected to reduce the risk of failure and enhance aesthetics. Given that approximately one in 15 patients have allergic reactions to antibiotics, photodynamic therapy (PDT) has been gaining attention as an alternative treatment. Herein, the applicability of PEEK dental implants or abutments was investigated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…Katzer discovered that PEEK fiber material is biocompatible and not cytotoxic to cells after incubating it with strains of Salmonella bacterium [36]. Moreover, Peng investigated biofilm growth on the surface of PEEK and discovered that it is less conducive to biofilm formation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Katzer discovered that PEEK fiber material is biocompatible and not cytotoxic to cells after incubating it with strains of Salmonella bacterium [36]. Moreover, Peng investigated biofilm growth on the surface of PEEK and discovered that it is less conducive to biofilm formation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have pointed out the potential of PAEK materials in dental applications, as their mechanical properties are close to those of human hard tissue and bone making them a good substrate for dental restorations and teeth [14,17]. Peng et al [43] evaluated the antibacterial effect of PAEK materials by testing their ability to form a biofilm. The results showed that PAEK did not easily generate biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Bone remodeling around dental implants is regulated according to the load applied on the implant fixture. Previous experiments that discussed the cytotoxicity of PEEK for MG-63 concluded that the cell metabolic activity of MG-63 on PEEK was similar to Ti-6Al-4V and Y-TZP [ 26 ]. Titanium dental implants are currently viewed as the gold standard in dental implantology.…”
Section: Discussionmentioning
confidence: 99%
“…Polizzi et al [ 43 ] indicated that chlorhexidine allows good control of the clinical indices. Peng et al [ 26 ] confirmed that the risk of bacterial biofilm of PEEK was less than that of Ti-6Al-4V, and that biofilm removal efficiency through treatment with photodynamic therapy on formed S. mutans and A. actinomycetemcomitans biofilms was more effective than with Ti-6Al-4V and Y-TZP [ 23 ]. PEEK had less reaction to bacteria and comparable biofilm removal ability via a non-antibiotic drug [ 26 , 43 ]; thus, replacing Ti-6Al-4V and Y-TZP with PEEK and PEKK might help alleviate inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation